Harmonizing Drying Time, Layer Thickness, and Drier Zones for Drying Kinetics: Quality and Safety of Solar Tunnel-Dried Wet-Processed Parchment Coffee (Coffea arabica L.) - Zenaba Kadir Abdissa; Yetenayet B. Tola; Addisalem Hailu Taye; Hayat Hassen Mohammed (International Journal of Food Science)
Tunnel solar dryer is the recently used drying method for better quality and safety of parchment coffee. However, the higher variation of drying temperature and RH along the long tunnel solar dryer results in a heterogeneous environment in the tunnel, which could make parchment coffee dried at different times or with different moisture contents. This study is aimed at investigating the effect of solar tunnel dryer zones at different zones of the dryer, divided into three zones from the inlet to the exit side of the drier and drying layer thicknesses on the drying time, drying kinetics, physicochemical, sensory, and fungal growth loads of parchment coffee. Furthermore, seven mathematical models were evaluated to select the best-fitting model for a specific zone to predict drying time. Results showed that dryer zones significantly (p<0.05) interacted with layer thickness for most of the measured parameters except titratable acidity and sensory properties. The dryer zone, coupled with the reduction in drying layer thickness, caused an increase in effective diffusivity and moisture removal rate and reduced drying time. The drying time to reach constant moisture content varied from 14 to 17 hours. Overall raw bean, cup, and total quality varied from 36.3 to 37, 48 to 51, and 84.3 to 87.3%, respectively. Values for physicochemical parameters ranged from 5.3 to 6.9 (pH), 2.1 to 2.6% (titratable acidity), 2.3 to 4.3°Brix TSS, 10.9 to 15.2% (ether extract), 39.2 to 53.5GAE/g (total phenolic content), and 38.5 to 59.2 (DPPH scavenging capacity). The fungal infection percentage at the end of drying varied from 4 to 93.3%, which could be associated with potential mycotoxin formation if recommended conditions were not maintained. In general, for better quality, similar drying times, and a lesser fungal load, it is recommended to use 4, 5, and 6 cm layer thickness in zones one, two, and three, respectively. The drying kinetics of parchment coffee in different dryer zones with different drying layer thicknesses showed variation. Zone one at 2 and 4 cm layer thicknesses is best described by the Verma model. Four- and six-centimetre layer thicknesses in zones 2 and 3 are best described by the modified Midilli model.